Phytochemical Investigation of New Algerian Lichen Species: Physcia Mediterranea Nimis - Marwa Kerboua; Monia Ali Ahmed; Nsevolo Samba; Radhia Aitfella-Lahlou; Lucia Silva; Juan F. Boyero; Cesar Raposo; Jesus Miguel Lopez Rodilla (Molecules, 2021)
The present study provides new data concerning the chemical characterisation of Physcia mediterranea Nimis, a rare Mediterranean species belonging to the family Physciaceae. The phytochemical screening was carried out using GC-MS, HPLC-ESI-MS-MS, and NMR techniques. Hot extraction of n-hexane was carried out, followed by separation of the part insoluble in methanol: wax (WA-hex), from the part soluble in methanol (ME-hex). GC-MS analysis of the ME-hex part revealed the presence of methylbenzoic acids such as sparassol and atraric acid and a diterpene with a kaurene skeleton which has never been detected before in lichen species. Out of all the compounds identified by HPLC-ESI-MS-MS, sixteen compounds are common between WA-hex and ME-hex. Most are aliphatic fatty acids, phenolic compounds and depsides. The wax part is characterised by the presence of atranorin, a depside of high biological value. Proton 1H and carbon 13C NMR have confirmed its identification. Atranol, chloroatranol (depsides compound), Ffukinanolide (sesquiterpene lactones), leprolomin (diphenyl ether), muronic acid (triterpenes), and ursolic acid (triterpenes) have also been identified in ME-hex. The results suggested that Physcia mediterranea Nimis is a valuable source of bioactive compounds that could be useful for several applications as functional foods, cosmetics, and pharmaceuticals.